2004
DOI: 10.1038/sj.onc.1207262
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of colon cancer by DNA microarrays and correlation with histoclinical parameters

Abstract: Different diagnostic and prognostic groups of colorectal carcinoma (CRC) have been defined. However, accurate diagnosis and prediction of survival are sometimes difficult. Gene expression profiling might improve these classifications and bring new insights into underlying molecular mechanisms. We profiled 50 cancerous and noncancerous colon tissues using DNA microarrrays consisting of B8000 spotted human cDNA. Global hierarchical clustering was to some extent able to distinguish clinically relevant subgroups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
186
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(202 citation statements)
references
References 89 publications
15
186
1
Order By: Relevance
“…They found several Rps (RPL5,L6,L15,L29,L31,L39) were down-regulated in metastatic CRC by oligonucleotide arrays detecting 50 colon adenocarcinomas and their paired normal mucosa [29]. The similar result appeared firstly in Cao's study in 1997 [30].…”
Section: Ribosomal Proteins and Colorectal Car-cinomasupporting
confidence: 70%
See 1 more Smart Citation
“…They found several Rps (RPL5,L6,L15,L29,L31,L39) were down-regulated in metastatic CRC by oligonucleotide arrays detecting 50 colon adenocarcinomas and their paired normal mucosa [29]. The similar result appeared firstly in Cao's study in 1997 [30].…”
Section: Ribosomal Proteins and Colorectal Car-cinomasupporting
confidence: 70%
“…Secondly, RPs showed different expression patterns: not the all RPs increased in the same tumor or tissue, and the same RP expressed differentially in different tumors or different stages of diseases. Thirdly, some RPs only increased in senescent cells, [38] some in quiescent cells and some in tumor cells well differentiated [31] but some decreased in metastatic CRC [29]. Fourthly, p53 mutation, a common event in CRC, which is considered the key factor in colon carcinogenesis can upregulate only several RPs but not all of them; [39] Fifthly, overexpression of specific RPs did not increase the synthesis of proteins [40].…”
Section: Extraribosomal Functions Of Rps In Cancermentioning
confidence: 99%
“…The transfection of nm23 cDNA into various cancer cell lines resulted in suppression of the metastatic potential of motility, invasion, or colonisation (Suzuki et al, 2004). However, Bertucci et al (2004) recently reported over-and downexpression of nm23 in colorectal cancer tissues and in those with poor prognosis, respectively. The reason why nm23 gene was highly expressed in tumour tissues in the current study may be due to the fact that all tumour samples We identified 22 genes the expression levels of which differed significantly in colorectal adenomas and early invasive carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Mainly advanced cancer has been analysed in gene expression profiling-based studies on colorectal cancer (Alon et al, 1999;Backert et al, 1999;Hegde et al, 2001;Kitahara et al, 2001;Notterman et al, 2001;Takemasa et al, 2001;Agrawal et al, 2002;Birkenkamp-Demtroder et al, 2002;Lin et al, 2002;Zou et al, 2002;Frederiksen et al, 2003;Muro et al, 2003;Tureci et al, 2003;Williams et al, 2003;Bertucci et al, 2004). Only a small number of adenoma and early invasive cancer tissues have been analysed in previous studies, and the issue of flat-and protruded-type adenoma tissues has not been directly addressed (Notterman et al, 2001;Agrawal et al, 2002;Lin et al, 2002;Williams et al, 2003).…”
mentioning
confidence: 99%
“…The potential complexity of genetic alterations in tumors renders microarray-based gene expression profiling a powerful tool for obtaining information about the molecular background of CRC, for establishing a relationship between the clinical and pathological stages and for discrimination of cellular conditions. Recently, gene expression signatures have been published, which classify Dukes' B and C CRC 6 as well as lymph-node-positive and negative CRC patients 7,8 based on analysis of bulk tissues. Agrawal et al used pooled samples to identify markers of colorectal tumor progression, 9 whereas Wang et al used gene expression analysis to predict recurrence of Dukes' B colon cancer.…”
mentioning
confidence: 99%